Key Opportunities to Replace, Reduce, and Refine Regulatory Fish Acute Toxicity Tests. (24th August 2020) - Burden, Natalie; Benstead, Rachel; Benyon, Kate; Clook, Mark; Green, Christopher; Handley, John; Harper, Neil; Maynard, Samuel K.; Mead, Chris; Pearson, Audrey; Ryder, Kathryn; Sheahan, Dave; et al.
Abstract: Fish acute toxicity tests are conducted as part of regulatory hazard identification and risk‐assessment packages for industrial chemicals and plant protection products. The aim of these tests is to determine the concentration which would be lethal to 50% of the animals treated. These tests are therefore associated with suffering in the test animals, and Organisation for Economic Co‐operation and Development test guideline 203 (fish, acute toxicity) studies are the most widely conducted regulatory vertebrate ecotoxicology tests for prospective chemical safety assessment. There is great scope to apply the 3Rs principles—the reduction, refinement, and replacement of animals—in this area of testing. An expert ecotoxicology working group, led by the UK National Centre for the Replacement, Refinement and Reduction of Animals in Research, including members from government, academia, and industry, reviewed global fish acute test data requirements for the major chemical sectors. The present study highlights ongoing initiatives and provides an overview of the key challenges and opportunities associated with replacing, reducing, and/or refining fish acute toxicity studies—without compromising environmental protection. Environ Toxicol Chem 2020;39:2076–2089. © 2020 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC.